Characterization of the Compounds Present in Bougainvillea x buttiana (var. Rose) with Healing Activity in a Murine Model - Luís Martínez-Cuevas; Mayra Cedillo-Cortezano; Blanca Nury Echeverria Guerrero; Rodolfo Abarca-Vargas; Vera L. Petricevich (Pharmaceuticals)
Background/Objective: Bougainvillea x buttiana of the Nyctagenaceae family is widely used in traditional Mexican medicine for treating different diseases. This study was planned to estimate the healing effect of the acetonic extract obtained from Bougainvillea x buttiana (var. Rose). Methods: The bracts with flowers were subjected to extraction using maceration and concentrated in vacuo. Fractionation with a similar profile resulted in 11 fractions, which were determined using TLC. A mouse wound excision model was tested to evaluate the wound healing effect of the topical treatment pre-formulated with fractions of acetonic extract, which were determined using image analysis techniques. Cytokine levels present in the sera of mice treated or not treated with the acetonic extract were determined using the ELISA method. Results: The results obtained showed that the crude acetonic extract of B. x buttiana and/or its fractions in a pre-formulated hydrogel had wound healing capacity. The wound contraction rate and the healing speed in groups of animals treated with the pre-formulated crude extract and/or its fractions were significantly higher compared with the negative control (p < 0.001). Fraction 2 demonstrated more significant healing, reduced the production of cytokines such as IL-6 and TNF-α, and enhanced the levels of IL-10. Conclusion: The present study showed that the fractions obtained from the acetonic extract of B. x buttiana bracts were able to accelerate the wound healing process through anti-inflammatory mechanisms by regulating inflammatory cytokines. The results presented demonstrate that the extracts from B. x buttiana contain compounds that may be responsible for their healing properties.